Improving selectivity to dinitrogen using Palladium-Indium coated on activated carbon fibers: Preparation, characterization and application in water-phase nitrate reduction using formic acid as an alternative reductant source. Issue 4 (August 2018) - Zoppas, F.M.; Bernardes, A.M.; Miró, E.; Marchesini, F.A.
Graphical abstract: Abstract: This work reports results on the preparation, characterization and application of activated carbon fibers as structured catalysts used in the decontamination of water containing nitrates. Activated carbon fibers were coated with Pd and In using sequential autocatalytic deposition. Besides, the efficiency of decontamination was evaluated when formic acid was used as a source of hydrogen. Different operating conditions were studied for conversion of nitrates to gaseous nitrogen in the aqueous phase, using Palladium and Indium as active phases. Concerning the selectivity to N2 of the catalysts evaluated at the same conversion (10%), all catalysts showed selectivity to gaseous nitrogen greater than 99%, demonstrating the high potential of carbon fibers as a structured catalyst support to nitrate reduction. The surface characteristics of the bimetallic catalyst were investigated by temperature-programmed oxidation, temperature-programmed reduction, dynamic H2 chemisorption, scanning electron microscopy, energy dispersive spectroscopy and X-ray diffraction showing that the metals were homogeneously distributed on the catalyst surface.